Cellular protein synthesis shutoff by mengovirus: translation of nonviral and viral mRNA's in extracts from uninfected and infected Ehrlich ascites tumor cells. - Abreu, S L (1976)
The mechanism whereby picornaviruses inhibit host protein synthesis while their own synthetic processes proceed unabated has remained elusive. One of our approaches to this problem was to study the ability of cell-free extracts derived from uninfected and mengovirus-infected Ehrlich ascites tumor cells to translate viral and nonviral mRNA's under various conditions of incubation. Our results indicate that viral messengers (from mengovirus and encephalomyocarditis virus) and cellular messengers [L cell and Ehrlich ascites tumor poly(A)-containing mRNA's, rabbit globin mRNA, and chicken embryo lens crystallin mRNA] are translated equally well in both extracts. We also examined the simultaneous translation of viral and nonviral mRNA's in extracts from uninfected Ehrlich ascites tumor cells. Our results indicate that under certain conditions mengovirus RNA can suppress completely the translation of globin mRNA. The significance of these results in terms of the shutoff of host protein synthesis is discussed.